EVALUATION BREAD WHEAT PURE LINES UNDER EFFECT OF DIFFERENT SEEDING RATES FOR GRAIN YIELD AND IT, S COMPONENT - & Naes, Baktash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was carried out at the Swerah Research Station –Office of Agricultural Researches Ministry of Agriculture, during 2014-2015 season. The objective of this research was to evaluation 15 pure lines (Triticum aestivum L.). genotypes ,the seventh generation developed by half dialled method between 6 parents. The experiment was conducted using split plot design with three replicates ,The main plots were four seeding rates (120, 160, 200 and 240 kg.ha-1 ), while the 21 genotypes occupied sub plots .The two pure lines S97 and S148 out yielded other genotypes except A4.10 and Abu-Ghraib in grain yield which, produced 6.35 and 6.09 t.ha-1, respecting .increasing seeding rates caused to increase in number of spikes .plant-1 and flag leaves angle. Significant difference were found among genotypes due to seeding rate.The pure line S148 ,using 200 kg.ha-1 seeding rate produced highest grain yield (7.49 t.ha-1) which did not differed from using A4.10 under 200 and 240 kg.ha-1 seeding rate. It was recommended to certify the pure line S148  using 200 kg.ha-1 seeding rate for cultivation at central of Iraq.